Glucose-Induced Production of a Penicillium Purpurogenum Xylanase by Aspergillus Nidulans - Levican-Jaque, G; Chavez-Rosales, R (Elsevier B.V., 2012)
The heterologous secretion of xylanase B from Penicillium purpurogenum using glucose as inducer was performed in Aspergillus nidulans. For this purpose, plasmid pEVXB, containing the xylanase B cDNA (including its own signal peptide) under the control of the glyceraldehyde-3-phosphate dehydrogenase promoter, was constructed and used to transform A. nidulans. Analysis of transformed clones showed that several of them secreted extracellular xylanase activity when grown in a medium containing glucose. The clone showing the highest xylanase activity was chosen for further work. When this clone was grown on glucose, xylanase activity (0. 72 U/ml), was detected in the culture supernatant. This was confirmed by a zymogram analysis and by the amplification of xynB cDNA from this clone. To our knowledge, this is the first example of the production of a xylanase from Penicillium in heterologous fungal hosts using glucose as inducer. © 2011 The Mycological Society of Japan and Springer.